Barriers to educational technology at high school level in Kolasib district (Mizoram) - Chuaungo2, S.Tamilenthi1* and Lalhmasai (Journal of Experimental Sciences, 2011)
The present investigation is intended to study the barriers to educational technology at high schools of kolasib district, Mizoram state. The professional development is based on educational technology is for teachers and the students for better of their education. The scale of barriers is constructed. Samples from 100 high schools teachers with normative survey and purposive sampling method. of statistical techniques were applied to draw the result. The personal variables were studied with respect to gender, educational qualification of the teacher., locality of the teacher and marital status of teaches were analysed with regard to the barriers like Psychological, Administrative, Teaching Technique, and Materials Barriers to Educational Technology. A significant difference was found in locality and educational qualifications. No difference was found in gender and marital status of the teachers.